Juridical Sufism: Zarruq’s Application of the Qawa‘id Genre - Shams-ur-Rehman, Ghulam (Islamic Studies, 2010)
Ahmad Zarruq (d. 899/1493) was one of the most important Shadhili Sufi scholars of North Africa. He successfully integrated the Sufi path with Islamic sacred law, managing to instil a measure of legal rectitude into popular devotional piety. The presentation of his concept of juridical Sufism using the Qawa‘id genre is Zarruq’s most important contribution to Sufi thought. In this paper I aim to examine the structure of his work Qawa‘id al-Tasawwuf and to analyse how he elaborates his Sufi thoughts through the medium of al-Qawa‘id al-fiqhiyyah. Following an investigation of the characteristics of legal adages, I shall demonstrate how Zarruq devised Sufi maxims upon their model, applying these pithy sayings to the specific context of Sufism. I shall further attempt to define the nature of Zarruq’s treatise, and to place it within the larger context of Sufi literature.